Abdullah Ahmad Badawi : jalan ke puncak - Sivamurugan Pandian (Cheras, Kuala Lumpur : Utusan Publications & Distributors, 2005)
Political account of Abdullah Ahmad Badawi, the fifth Prime Minister of Malaysia
Bibliography : p. 67-69
Keywords: Abdullah Haji Ahmad Badawi, -- Dato' Seri, -- 1939-; Prime ministers -- Malaysia -- Biography; Politician -- Malaysia -- Biography; Malaysia -- Politics and government